HUBUNGAN POLA MAKAN, KUALITAS TIDUR, DAN MENSTRUASI DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMA NEGERI 2 TAMBUN SELATAN TAHUN 2022 - Nana Alyarahmah (2022)
Adolescents with anemia are one of the major public health problems. There are several factors that can cause adolescents to have anemia, such as diet pattern, sleep quality, and menstruation. The purpose of this study was to find whether there are any relationship between diet pattern, sleep quality, and menstruation with anemia in adolescent girls at SMA Negeri 2 Tambun Selatan. This study used cross-sectional with purposive and simple random sampling design. There are a total of 49 people aged 15-18 years old as respondents. Data were collected using the easy-touch GCHb tool, 24-hour food recall form, SQ-FFQ, PSQI, and menstruation questionnaire. Data were analyzed using the Chi-Square test. The result of the study showed there was a correlation between protein intake (p = 0,004), iron intake (p = 0,035), and sleep quality (p = 0,004) with anemia, and there was no correlation between energy intake (p = 0,073), menstrual cycle (p = 0,861), and menstruation duration (p = 0,25) with anemia.